Surgical treatment and histopathological analysis of proptosis - Rizvi, SAR; Gupta, Y; Gupta, M (Nepalese Journal of Ophthalmology, 2010)
Introduction: Inflammations and tumors of the orbit and para-orbital regions may present as proptosis. Management depends on clinical, radiological, histo-pathological and biochemical evaluation. Objective: To analyze the clinical and histopathological profile of the lesions causing proptosis and to report the outcome of their surgical management. Materials and methods: In a retrospective study, 25 cases of proptosis due to orbital and paraorbital tumours were analyzed in relation to their age, sex, and clinical and histopathological profiles. CT Scan was considered as the first line investigation modality. According to location and type of tumour, different surgical options like anterior orbitotomy, lateral orbitotomy and medial orbitotomy were considered. Results: The majority of the patients were of the age group 50-59 years (28 %). Primary orbital tumors were encountered in 15 cases (60 %) and para-orbital in 10 (40 %). Of 15 primary orbital tumors, 7 (46.66 %) were excised by lateral orbitotomy, another 7 (46.66 %) were approached via anterior orbitotomy, whereas 1 (6.67%) was removed by medial orbitotomy. Pediatric orbital tumors were quite common 7(46.66%). Three cases of rhabdomyosarcoma, 3 cases of dermoid cyst and 1 case each of optic nerve glioma were found in pediatric age group. The most common benign adult tumor found in our study was pleomorphic adenoma of the lacrimal gland 3(20%). Conclusion: The majority of the patients with proptosis are of the age group 50-59 years. Proptosis due to primary orbital tumors is more common than para-orbital tumors. Early diagnosis and timely surgical intervention provide good functional and cosmetic results. Keywords: orbit; proptosis; tumors; orbitotomy. DOI: 10.3126/nepjoph.v2i1.3701 Nep J Oph 2010;2(1):31-34